1990
DOI: 10.1111/j.1528-1157.1990.tb05517.x
|View full text |Cite
|
Sign up to set email alerts
|

Landau‐Kleffner Syndrome: A Clinical and EEG Study of Five Cases

Abstract: In five children with normal initial psychomotor development, a Landau-Kleffner syndrome appeared at age 3-7 years. No neuroanatomic lesions were noted. Aphasia and hyperkinesia were isolated in three patients and associated with global regression of higher cortical functions in one patient. Massive intellectual deterioration and psychotic behavior were associated with transient aphasia in one patient. The epilepsy (focal motor and generalized tonic-clonic seizures, subclinical EEG focal seizures during sleep,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
8

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(108 citation statements)
references
References 22 publications
1
99
0
8
Order By: Relevance
“…In LKS, structural brain abnormality is uncommon. Both computed tomography and MRI are usually normal (13,(18)(19)(20)(21)(22).…”
Section: Seizures and Screening In Lksmentioning
confidence: 99%
See 1 more Smart Citation
“…In LKS, structural brain abnormality is uncommon. Both computed tomography and MRI are usually normal (13,(18)(19)(20)(21)(22).…”
Section: Seizures and Screening In Lksmentioning
confidence: 99%
“…Lagae (26), in his recent review indicated the use of antiepileptic drugs (AEDs) as the first-line treatment, including VPA and ethosuximide. However, a number of reports have shown that the early use of steroids, including prednisone, methylprednisolone and/or andrenocorticotropic hormone (ACTH) are effective in improving both the EEG abnormality and language (18,(27)(28)(29)(30)(31). Series published to date used very different schemes of steroid treatment, different dosing and time course, making comparisons difficult.…”
Section: Treatmentmentioning
confidence: 99%
“…However, other investigators described fluctuating neurological symptoms, disturbed speech and cognitive impairment that were related to the presence of frequent IEDs but not strictly time-locked to them. Drug treatment that abolished the spikes caused significant clinical improvement within a short time period (Hirsch et al, 1990;Metz-Lutz et al, 1999;Baglietto et al, 2001;Massa et al, 2001;Dalla Bernardina et al, 2002). Thus, a "delayed effect" of the IEDs might be deductively postulated as an explanation for the lack of the precise temporal coincidence between the IEDs and the time course of the above mentioned symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in other recent studies despite promising logarithm of odds (LOD) scores, no genetic mutations have been identified [31,32]. Recent studies in some families has shown an overlap between epileptic encephalopathy with CSWS, atypical benign partial epilepsy, and BECTS which has led to the concept of a spectrum of epilepsy-aphasia disorders with BECTS at the lower end, the broad less well-defined group of epilepsy-aphasia children in the middle, and classical LKS and the syndrome of CSWS at the extreme end [30,[33][34][35]. This overlap suggests an additional genetic as well as environmental factors which determine whether the spectrum of disease will manifest as BECTS or as epileptic-aphasia spectrum disorder.…”
Section: Geneticsmentioning
confidence: 99%